The Influence of Profitability, Intermediation Function, and Leverage on Firm Value - Muhammad Adam Aptiansyah; Laeli Budiarti (Universitas Tidar, 2025)
This study examines the relationship between profitability, intermediation performance, leverage, and firm value among banking companies listed on the Indonesia Stock Exchange (IDX) during the 2022–2024 period. The research adopts the PBV ratio as its primary measure of firm value. For the explanatory variables, we selected ROA to represent profitability, LDR for the intermediation function, and DER as our leverage indicator. Drawing on Signaling Theory, the study considers these financial ratios as key indicators that investors may interpret when assessing bank performance and risk. An analysis of panel data from 26 banking companies (comprising 78 observations) determined that the Random Effects Model was the best statistical method for this study. Profitable banks receive substantially higher market valuations compared to their less profitable counterparts. The magnitude of this relationship underscores how critically investors evaluate earnings when determining a bank's worth. On the contrary, banks with higher lending to deposit ratios experience lower market valuations, as excessive lending activity may signal potential liquidity problems and weaken investor sentiment. Interestingly, the level of leverage does not significantly influence how the market values these banking institutions. Overall, the findings highlight that not all financial ratios carry equal weight as market signals and emphasize the importance of maintaining profitability and prudent intermediation practices in the post pandemic banking environment.